2011
DOI: 10.1080/00222348.2010.549074
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Poly(tetrafluoroethylene) Microporous Membranes by Acrylic Acid Liquid-Phase Graft Copolymerization

Abstract: Air plasma-pretreated poly(tetrafluoroethylene) (PTFE) films were subjected to further surface modification by liquid-phase graft copolymerization with acrylic acid monomer (AAc). The surface compositions and microstructures of the modified films were characterized by X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM). An exterior graft copolymerization of AAc on the PTFE fiber was indicated by the SEM photographs. The XPS results indicated that the F/C atomic ratio of the membranes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Numerous efforts have been made to enhance PTFE surface polarity and wettability for higher permeate flux of filtration processes, such as chemical oxidation treatment , wet‐chemical method , , gaseous plasma treatment , and irradiation graft polymerization . Most of these methods were only carried out on flat PTFE membranes by means of complicated instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous efforts have been made to enhance PTFE surface polarity and wettability for higher permeate flux of filtration processes, such as chemical oxidation treatment , wet‐chemical method , , gaseous plasma treatment , and irradiation graft polymerization . Most of these methods were only carried out on flat PTFE membranes by means of complicated instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Different techniques have been introduced to improve the wetting and adhesion properties of PTFE surfaces. Examples of these techniques are plasma, radiation [18][19][20] and chemical treatment [21]. Utsumi et al [20] enhanced bonding characteristics of PTFE surfaces using x-ray photo decomposition desorption and ablation and showed that PTFE changes state and exhibits hydrophilic characteristics after exposure to high-energy photons.…”
Section: Introductionmentioning
confidence: 99%